PENGARUH PARTISIPASI MASYARAKAT DAN ADVOKASI WALHI DIY TERHADAP KEPUASAN PEMBUATAN RTH KRICAK - Lestari, Lara Ayu; Perwitasari, Dyah Rahayuning; Bato, Bulan Erika; Zana, Iqbal Saputra; Perdana, Gusti Naufal Rizky (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
This Study Aims To Analyze The Influence Of Community Participation and advocacy by WALHI DIY on community satisfaction in the process of creating Green Open Spaces (RTH) in Kricak Village, Yogyakarta City. The research method used is a quantitative approach with an Ex-Post Facto design, which aims to examine the relationship between community participation, WALHI DIY advocacy, and community satisfaction. Data were collected through questionnaires distributed to 160 residents in Kricak Village and analyzed using multiple linear regression. The results show that both community participation in the RTH development process and the advocacy carried out by WALHI DIY have a significant impact on the level of community satisfaction. Community participation in the planning and implementation of RTH development increases a sense of ownership of the project, while advocacy by WALHI DIY enhances community understanding of the importance of RTH and how the process can improve their quality of life. This finding provides an important contribution to the development of more participatory RTH development policies, where the community is actively involved, and policies that support environmental sustainability. This research is expected to serve as a reference in the implementation of more inclusive green space development policies that have a positive impact on the community.